Ejaculation in testicular cancer patients after post-chemotherapy retroperitoneal lymph node dissection - Jacobsen, K D (Nature Publishing Group, 1999)
The purpose of this study was to evaluate fertility after different types of post-chemotherapy retroperitoneal lymph node dissection (RPLND). During 1980–1994, 192 patients with metastatic testicular cancer underwent post-chemotherapy RPLND with a gradual shift from modified bilateral template RPLND to nerve-sparing RPLND. Modified bilateral template RPLND was done in 92% of the patients operated during 1980–1984 as compared to 16% during 1989–1994. Pre- and post-treatment fertility was assessed by microscopic sperm analysis, determination of serum FSH and information on ejaculation and paternity. There was no significant difference of the survival rates between the three treatment periods. Antegrade ejaculation was preserved in 11% of the patients after modified bilateral template RPLND as compared to 89% after the nerve-sparing operation technique. The median ejaculatory volume decreased post-operatively, serum FSH increased and sperm density remained unchanged. Fifty-six patients attempted fatherhood after their treatment, and 27 fathered at least one child after an observation-time of 55 months, nine of them by assisted fertilization. Patients with initially advanced testicular cancer but limited residual retroperitoneal masses after induction chemotherapy can safely undergo limited post-chemotherapy RPLND as a part of multimodality treatment. After nerve-sparing RPLND antegrade ejaculation is preserved in 89% of the patients though the ejaculatory volume decreases after RPLND. Post-treatment fatherhood can be achieved in at least 50% of the patients attempting paternity. © 1999 Cancer Research Campaign